2021
DOI: 10.3390/diagnostics11081479
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Bronchoscopy for Peripheral Pulmonary Lesion Biopsy: Evidence-Based Review of the Two Platforms

Abstract: Despite many advancements in recent years for the sampling of peripheral pulmonary lesions, the diagnostic yield remains low. Initial excitement about the current electromagnetic navigation platforms has subsided as the real-world data shows a significantly lower diagnostic sensitivity of ~70%. “CT-to-body divergence” has been identified as a major limitation of this modality. In-tandem use of the ultrathin bronchoscope and radial endobronchial ultrasound probe has yielded only comparable results, attributable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The limitations of this study would be related primarily to the relatively single-arm non-randomized design, small sample size, single-center, retrospective study, and the 42 cases were performed by a single operator in a large university setting. We also believe that for other operators who do not perform this procedure often, there is a potential inability to generalize the results [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of this study would be related primarily to the relatively single-arm non-randomized design, small sample size, single-center, retrospective study, and the 42 cases were performed by a single operator in a large university setting. We also believe that for other operators who do not perform this procedure often, there is a potential inability to generalize the results [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, the existing endotracheal tube was connected to the robotic bronchoscopy system. The robotic bronchoscopy system consists of a tower with a monitor and a unit with arms that can insert, retract, and articulate an outer sheath (with an outside diameter of 6.0 mm) and an inner scope (with an outer diameter of 4.4 mm and a working channel of 2.1 mm) [ 16 ]. A 3D segmented airway model was produced by the Ion Plan Point Planning Station using data from a recent preoperative CT scan, which facilitated navigating to and locating the lesion.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, the systems feature a bronchoscope with enhanced articulation and an integrated navigation system that guides the bronchoscope pathway inside the airways. A previous review of currently available two robotic surgical systems for bronchoscopic surgeries: Monarch 1 and ION 1 is presented in [172].…”
Section: Bronchoscopic Surgerymentioning
confidence: 99%
“…In a randomized trial, the 3-mm ultrathin bronchoscope provided higher diagnostic yields for pulmonary lesions than the 4-mm thin bronchoscope combined with radial endobronchial ultrasound, VBN, and fluoroscopy (70.1% vs. 58.7%) [3] . Recently, a retrospective study showed that robot-assisted bronchoscopy appeared to be a promising approach, with a successful navigation yield of 88.6%, diagnostic yield of 69.1% to 77.0%, and pneumothorax rate of 3.6% [4] . However, these approaches were restricted to nodules in which a BS was present.…”
mentioning
confidence: 99%